Functional characterization of transcriptional enhancers in an Anopheles genetic locus controlling natural resistance to the malaria parasite, Plasmodium falciparum - Natalia Marta Zmarlak-Feher; Kathryn S. Taquet; Renée Zakhia; Adrien Pain; Emma Brito-Fravallo; Cameron E. Anderson; Kenneth D. Vernick; Christian Mitri; Michelle M. Riehle (Epigenetics & Chromatin)
Abstract Background Anopheles mosquitoes and the malaria parasites they transmit remain a significant global health problem. Most genomic and functional genomic studies of mosquitoes have focused on the protein-coding genome, and comparatively little is known about the importance of noncoding transcriptional enhancers in controlling their gene expression and phenotypic variation. Here we evaluate nine enhancers previously identified in a STARR-seq screen and present in a genetic locus that was identified as a major influence on susceptibility to malaria infection in wild Anopheles coluzzii mosquitoes. Result We developed an analytical pipeline to filter nine enhancers in the malaria susceptibility locus on chromosome 2L. First, ATAC-seq revealed that only three of the nine enhancers were located in open chromatin and thus likely to be active in somatic cells. Next, we cloned these three enhancers from malaria-susceptible and resistant mosquitoes and measured their enhancer activity by luciferase reporter assays. Only two of the three open-chromatin enhancers displayed significantly different enhancer activity between resistant and susceptible alleles. Finally, alleles of just one of these enhancers, ENH_2L-03, contained nucleotide variants which also segregated in wild mosquitoes, and ENH_2L-03 was prioritized for further study. A noncoding RNA was detected within ENH_2L-03, consistent with an enhancer RNA (eRNA), which we depleted in mosquitoes using RNAi in order to silence the enhancer activity. Transcriptional profiling of ENH_2L-03-silenced mosquitoes revealed 15 differentially expressed genes, which share a transcription factor binding motif suggestive of coordinate regulation. However, silencing ENH_2L-03 did not influence infection levels of either human or rodent malaria parasites. Conclusion Despite the absence of an ENH_2L-03 effect on infection outcome, multiple enhancers can cooperate to influence a phenotype, and further examination of this enhancer is warranted. Overall, we provide a pipeline for the in vivo functional study of transcriptional enhancers in Anopheles, towards understanding how enhancer function may control important vector phenotypes.